Analisis Persepsi Calon Guru Terhadap Pengembangan Keterampilan Probem Solving Melalui Pembelajaran Fisika - Erwin, Erwin; Rustaman, N Y; Firman, H; Ramalis, T R (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
A study about development of problem solving skills in physics learning was conducted to investigate how prospective teachers were able to integrate this ability into physics instruction. This article discusses the responses of prospective teachers to the development of problem solving skills through physics learning. Data were collected by using questionnaires and interviews. To strengthen data obtained through questionnaires, data were analyzed descriptively. The results of the study show that prospective physics teachers who have participated in Field Experience Program 2 (PPL 2) or who are currently participating in PPL 1, in general, agree that problem solving skills can be developed through subject matter learning, especially in physics learning. However, there are some prospective physics teachers who gave anomalous responses to several statements in the questionnaire, for example there are students who do not approve the statement that reads “Facilitating and analyzing problems for problem solving is done by drawing or sketching”. Based on these findings, it is necessary to provide a good understanding of the steps that should be taught in developing problem solving skills, such as giving example or modelling. Furthermore, prospective physics teachers need to be assessed their ability to teach the development of problem solving skills which was integrated with/in physics learning.